Die sowjetische Kinderliteratur als Katalysator imaginierter Gemeinschaft zwischen Kuba und Osteuropa - Thaidigsmann, Karoline (Zeitschrift für Slawistik, 2025)
For the past decade, research on Cuba has increasingly focused on the cultural influences of Soviet-style socialism and its persistence in contemporary Cuba. On the part of Eastern European studies, the cultural relations between the two regions and the perception of Cuba in Eastern European cultures have been neglected for a long time. With regard to children’s culture such studies are lacking entirely. During socialism, however, children’s culture became a catalyst of imagined community between the countries of Eastern Europe and Cuba. Using examples from Soviet children’s literature the article examines the differing strategies used by authors of children’s literature to portray this relationship. Thereby it becomes apparent that the narratives do not only serve the creation of an imagined community with Cuba, but also the self-perception of Soviet society - either in a reinforcing or self-critical way. To this end the authors make use of the metaphorical and real opposition between children and adults familiar from colonial and imperialist discourses.
Online veröffentlicht: 22. Mai 2025
Gesehen am 21.01.2026